2004
DOI: 10.1007/s10120-004-0280-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in thymidylate synthase and its inhibition rate and changes in dihydropyrimidine dehydrogenase after the administration of 5-fluorouracil with cisplatin to nude mice with gastric cancer xenograft SC-1-NU

Abstract: Combined administration of cisplatin with 5-FU did not further increase thymidylate synthase inhibition over that occurring with 5-FU alone, which does not support the hypothesis that cisplatin combined with 5-FU modulates thymidylate synthase inhibition in enhancing the anticancer effect of 5-FU. Changes in DPD after the administration of 5-FU may provide an insight into tumor sensitivity and resistance to 5-FU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…34 Moreover, nude mice studies with human gastric cancer xenografts also demonstrated a dramatic decrease in DPD activity after short-term exposure to 5FU. 35 In line with the latter reports, our data show that DPD mRNA expression in primary tumors is down regulated by 5FU. Further investigations have to bring more light on the mechanism behind this 5FU-induced down regulation of DPD.…”
Section: Discussionsupporting
confidence: 81%
“…34 Moreover, nude mice studies with human gastric cancer xenografts also demonstrated a dramatic decrease in DPD activity after short-term exposure to 5FU. 35 In line with the latter reports, our data show that DPD mRNA expression in primary tumors is down regulated by 5FU. Further investigations have to bring more light on the mechanism behind this 5FU-induced down regulation of DPD.…”
Section: Discussionsupporting
confidence: 81%
“…GC cells (5 × 10 6 ) with HOXA13 knockdown or DHRS2 overexpression were suspended in 100 µL of PBS and subcutaneously injected into flanks of the mice. Seven days after subcutaneous inoculation, the mice were randomly divided into two groups (3 mice/group) and injected with either PBS or 5‐FU (20 mg/kg/day) by intraperitoneal injection every other day for 11 days (i.e., 6 injections) . Tumor volume (mm 3 ) was estimated weekly by using the following formula: tumor volume (mm 3 ) = length × width 2 × 0.5 .…”
Section: Methodsmentioning
confidence: 99%
“…The mice were euthanized 2 days after the final injection, and the intraperitoneal tumors were then removed and weighed. The doses of these inhibitors were based on previous reports (18)(19)(20). All animal studies were conducted using protocols approved by Kumamoto University Institutional Animal Care and Use Committee.…”
Section: In Vivo Chemoresistance Assaymentioning
confidence: 99%